1997
DOI: 10.1111/j.1528-1157.1997.tb01255.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Claustrum in Convulsive Evolution of Visual Afferent and Partial Nonconvulsive Seizure in Primates

Abstract: Summary: Purpose: We tested cross-species validity of the role of the claustrum in the convulsive evolution of the visual afferent and amygdaloid seizure and the specificity of the claustral lesioning effect.Methods: In 7 Senegalese baboons, we examined the effect of unilateral claustral lesioning on generalized convulsive seizures either kindled from the amygdaloid nucleus (AM) and cingulate cortex (CG) or induced by intermittent photic stimulation (IPS) after systemic administration of D,L-allylglycine (AG).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…Thus Kudo and Wada (1990) found that electrolytic lesions of the cat anterior claustrum ipsilateral to the kindled amygdala degraded generalized kindled seizures to partial seizures and retarded kindling. Similar results have also been observed in monkeys (Wada and Tsuchimochi, 1997). Radio-frequency (RF) lesions of the posterior claustrum delay amygdaloid kindling in rats (Mohapel et al, 2001).…”
Section: Abstract: Kindling; Epilepsy; Seizure; Claustrum; Pha-l; Flsupporting
confidence: 71%
“…Thus Kudo and Wada (1990) found that electrolytic lesions of the cat anterior claustrum ipsilateral to the kindled amygdala degraded generalized kindled seizures to partial seizures and retarded kindling. Similar results have also been observed in monkeys (Wada and Tsuchimochi, 1997). Radio-frequency (RF) lesions of the posterior claustrum delay amygdaloid kindling in rats (Mohapel et al, 2001).…”
Section: Abstract: Kindling; Epilepsy; Seizure; Claustrum; Pha-l; Flsupporting
confidence: 71%
“…Indeed, the claustrum could be a key region in promoting the propagation and synchronization of abnormal epileptic activity from several cortical regions (12, 32). Two properties of claustrum neurons are relevant: (a) claustro-cortical fibers connect the claustrum with several cortical areas including the prefrontal, pre-postcentral, orbitofrontal, and medial temporal cortex (33, 34); (b) the claustrum is constituted by densely packed and tightly interconnected GABAergic interneurons whose damage could promote a state of hyper-synchronization and bindings of activity from several distant cortical regions (3438). Notably, these experimental findings can account for the frequently observed presence of PD over one or both hemispheres during continuous EEG monitoring in our patients, as well as the often bi-hemispheric or independent seizure origin during the acute phase.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that even a light projection entering these regions can be extensively distributed within the area and influence brain regions targeted by these nuclei. This might explain why the claustrum and the endopiriform nucleus are implicated as brain areas by means of which seizure activity originating in the temporal lobe can rapidly spread to various extratemporal regions (Kudo and Wada, 1990; Mohapel and Corcoran, 1996; Wada and Kudo, 1997; Wada and Tsuchimochi, 1997; Mohapel et al, 2000).…”
Section: Discussionmentioning
confidence: 99%